2019
DOI: 10.1002/lio2.254
|View full text |Cite
|
Sign up to set email alerts
|

The role of intravenous acetaminophen in post‐operative pain control in head and neck cancer patients

Abstract: Objective This study investigated the role of intravenous acetaminophen for alleviation of postoperative pain after surgical resection of head and neck cancers. Methods A single‐center study was conducted, which investigated a prospective group of 48 participants who underwent surgery between April 2016 and May 2017 and postoperatively received scheduled IV acetaminophen (1 g every 6 hours for 4 doses) plus the standard opioid PCA and breakthrough narcotics. These were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…The average score was 15.1 ± 1.6, with all studies reporting a clearly stated aim, end points appropriate to study aim, follow-up period appropriate to study aim, and an adequate control group. Five studies 15-18,20 included consecutive patients while 1 study 21 included prospective data collection with the other studies comparing against historical data. Only 1 study performed a prospective calculation of study size.…”
Section: Resultsmentioning
confidence: 99%
“…The average score was 15.1 ± 1.6, with all studies reporting a clearly stated aim, end points appropriate to study aim, follow-up period appropriate to study aim, and an adequate control group. Five studies 15-18,20 included consecutive patients while 1 study 21 included prospective data collection with the other studies comparing against historical data. Only 1 study performed a prospective calculation of study size.…”
Section: Resultsmentioning
confidence: 99%
“…25 Alternative pain regimens show promise (eg, acetaminophen, gabapentin, celecoxib, lidocaine), but more studies are needed in patients with head and neck cancer. [26][27][28][29][30][31] During this study period, there was not a specific institutional protocol for pain management during or after treatment. However, following the results of this study, we have implemented the prophylactic use of gabapentin during RT as well as increased utilization of alternative pain regimens perioperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that intravenous acetaminophen spares opioid use and reduces postoperative pain. 6,[18][19][20] A recent study in elderly patients recovering from cardiac surgery reported that intravenous acetaminophen decreased opioid consumption and reduced delirium. 21 .…”
Section: Discussionmentioning
confidence: 99%